Xpert MTB/RIF Ultra for Tuberculosis Testing in Children: A Mini-Review and Commentary - Atherton, Rachel R.; Cresswell, Fiona V.; Ellis, Jayne; Kitaka, Sabrina B.; Boulware, David R. (Frontiers in Pediatrics, 2019)
Tuberculosis (TB) remains a significant, yet under-recognised cause of death in the paediatric population, with a WHO estimate of 1 million new cases of childhood TB in 2016 resulting in 250,000 deaths. Diagnosis is notoriously difficult; manifestations are protean due to the high proportion of cases of extra-pulmonary TB in children, and logistical problems exist in obtaining suitable specimens. These issues are compounded by the paucibacillary nature of disease with the result that an estimated 96% of paediatric TB-associated mortality occurs prior to commencing anti-tuberculous treatment. Further development of sensitive, rapid diagnostic tests and their incorporation into diagnostic algorithms is vital in this population, and central to the WHO End-TB strategy. Initial gains were made with the expansion of nucleic acid amplification technology, particularly the introduction of the GeneXpert fully-automated PCR Xpert MTB/Rif assay in 2010, and more recently, the Xpert MTB/Rif Ultra (Ultra) assay in 2017. Ultra provides increased analytical sensitivity when compared with the initial Xpert assay in vitro; a finding now also supported by six clinical studies to date, two of which included paediatric samples. Here, we review the published evidence for the performance of Ultra in TB diagnosis in children, as well as studies in paucibacillary adults providing results relevant to the paediatric population., and consider the relevance of Ultra for pauci-bacillary TB, such as occurs in paediatric populations. Following on from this, Wwe also speculate upon review the future directions for Ultra, with focus on its potential use with alternative diagnostic specimens, which may be of particular utility in children.